DBU-mediated diastereoselective aldol-type cyanomethylation of isatins - Rao, V. U. Bhaskara; Kumar, Krishna; Das, Tamal; Vanka, Kumar (Journal of Organic Chemistry, 2017)
An efficient, metal-free approach to 3-substituted 3-hydroxybxindole by DBU-mediated highly diastereoselective addition of aryl acetonitrile to N-protected isatin under mild conditions has been developed. The reaction proceeds smoothly to produce respective cyanomethylated adducts in good yield and excellent diastereoselectivity. Further transformation of the cyanide group allowed the synthesis of an advance intermediate of corresponding (+/-) CPC analogue. The mechanistic insight :toward the aldol-type cyanomethylation, of N-tritylisatin with benzyl cyanide was obtained by DFT calculations.

Dual mode selective detection and differentiation of TNT from other nitroaromatic compounds - Patil, Goudappagouda; Dongre, Sangram D.; Das, Tamal; Babu, Sukumaran Santhosh (Journal of Materials Chemistry A, 2020)
Selective detection of explosives, especially TNT, is a highly desirable area of research and various explosives detection devices including fluorescent sensors are already in place. However, multi-mode sensors will be more useful and reliable than conventional fluorescent ``Turn Off'' sensors. One of the challenges is the development of selective sensors to prevent illegal transport of commonly used explosive TNT through on-the-spot analysis. In this context, we report a fluorescent polymer-based selective detection of TNT using both fluorometric and colorimetric signals. In addition, colorimetric differentiation of TNT from other nitroaromatic compounds is made possible by complexing with various amines. Even though many other sensors are available for TNT, the current demonstration is unique in terms of selectivity, sensitivity, reliability, portability, and rapidity of results. The as-developed explosive detection kit can be useful in both civilian and military operations to trace the illegal transport of TNT as well as for post-explosion analysis.

Diverse reactivity of carbenes and silylenes towards fluoropyridines - Kundu, Gargi; Ajithkumar, V. S.; Bisai, Milan Kumar; Tothadi, Srinu; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2021)
The reaction of IDipp with C5F5N led to functionalization of all three carbon atoms of the imidazole ring with HF2- as the counter-anion (1). Reactivity with 2,3,5,6-tetrafluoropyridine gives only C-F bond activation leaving C-H bonds intact (5b). The reaction of SIDipp with C5F5N in the presence of BF3 afforded the ring cleavage product (3). Analogous reactions with silylene led to oxidative addition at the Si(II) center.